What is intelligence? beyond the Flynn effect - Flynn 1934 (Cambridge University Press, 2007)
This book bridges the gulf that separates our minds from those of our ancestors a century ago. It is a fascinating and unique book that makes an important contribution to our understanding of human intelligence.